Preclinical safety profile of disitamab vedotin：a novel anti-HER2 antibody conjugated with MMAE. (15th May 2020) - Jiang, Jing; Li, Shenjun; Shan, Xiaolei; Wang, Ling; Ma, Jinling; Huang, Min; Dong, Lihou; Chen, Fang
Highlights: The toxicities associated with Disitamab vedotin were well characterized. Disitamab vedotin was well tolerated in preclinical studies in cynomolgus monkeys, the highest non-severely toxic dose was 6 mg/kg in repeated dose toxicity studies. Disitamab vedotin toxicities are hematology toxicity that related to monomethyl auristatin E(MMAE) mechanisms of action and pharmacologic activity, consistent with major side effects found in clinical trials. When conjugated in Disitamab vedotin, higher doses of MMAE can be tolerated. The therapeutic window for cytotoxic agents was improved by antibody-drug conjugates. Abstract: The HER2 pathway plays a pivotal role in cell proliferation and differentiation, while the receptor overexpression caused by amplification of HER2 gene is associated with the growth of several tumors. Previously published clinical trials have demonstrated that antibody-conjugated drugs (ADCs) remarkably improved clinical effects compared with antibodies alone for the same target. In order to provide more effective drugs, we developed Disitamab vedotin based on ADC. The antibody part was a humanized monoclonal antibody targeting HER2, the small molecule toxin was monomethyl auristatin E (MMAE), a synthetic antineoplastic agent. A protease cleavable linker covalently attached MMAE to the antibody. In this study, we characterized the toxicity profile of Disitamab vedotin through single- and repeat-dose toxicity studies in monkeys. The toxicities of small molecules and naked antibody (Disitamab) were also assessed in these studies. Monkeys were well tolerated with Disitamab vedotin at doses of 6 mg/kg, while equivalent MMAEs resulted in severe myelosuppression. This finding proves that ADCs improve the therapeutic effect. In addition, the safety profiles of Disitamab vedotin and MMAE were similar and consistent with the activation mechanism of MMAE. Toxicology finding included bone marrow/hematology toxicity and lymphoid organ toxicity, while no significant toxicity was observed in animals treated with naked antibody. These side effects were found to be consistent with data acquired from clinical phase I/II patients treated with Disitamab vedotin.